2010
DOI: 10.1093/jnci/djq025
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression-Based Prognostic Signatures in Lung Cancer: Ready for Clinical Use?

Abstract: A substantial number of studies have reported the development of gene expression-based prognostic signatures for lung cancer. The ultimate aim of such studies should be the development of well-validated clinically useful prognostic signatures that improve therapeutic decision making beyond current practice standards. We critically reviewed published studies reporting the development of gene expression-based prognostic signatures for non-small cell lung cancer to assess the progress made toward this objective. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
316
2
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(325 citation statements)
references
References 36 publications
4
316
2
3
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16][17]. However, a recent review critically evaluated the suggested signatures and concluded that in general they do not provide additional prognostic information compared with traditional clinical parameters (18). Some prognostic multigene signatures have been confirmed in independent datasets (14)(15)(16), but the impact of individual genes has rarely been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17]. However, a recent review critically evaluated the suggested signatures and concluded that in general they do not provide additional prognostic information compared with traditional clinical parameters (18). Some prognostic multigene signatures have been confirmed in independent datasets (14)(15)(16), but the impact of individual genes has rarely been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Early detection of cancer has been reported to greatly improve both the survival rate and prognosis, suggesting that the key to oncotherapy may lie in early diagnosis (3)(4)(5)(6)(7). Thus, developing a method for the early detection of cancer is both important and necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Понятие о молекулярной сигнатуре возникло относи-тельно недавно в качестве альтернативного направле-ния протеомного анализа и активно развивается [8,9]. Сигнатура включает в себя набор качественно или количе-ственно оцениваемых молекулярных параметров, напри-мер генетических полиморфизмов, уровня экспрессии транскриптов, белков, содержания липидов или других метаболитов, измерение которых обеспечивает высокую точность диагностики заболевания [10].…”
Section: Introductionunclassified